Drosophila NMNAT Maintains Neural Integrity Independent of Its NAD Synthesis Activity - Zhai, R. Grace (Public Library of Science, 2006)
Wallerian degeneration refers to a loss of the distal part of an axon after nerve injury. Wallerian degeneration slow (Wld(s)) mice overexpress a chimeric protein containing the NAD synthase NMNAT (nicotinamide mononucleotide adenylyltransferase 1) and exhibit a delay in axonal degeneration. Currently, conflicting evidence raises questions as to whether NMNAT is the protecting factor and whether its enzymatic activity is required for such a possible function. Importantly, the link between nmnat and axon degeneration is at present solely based on overexpression studies of enzymatically active protein. Here we use the visual system of Drosophila as a model system to address these issues. We have isolated the first nmnat mutations in a multicellular organism in a forward genetic screen for synapse malfunction in Drosophila. Loss of nmnat causes a rapid and severe neurodegeneration that can be attenuated by blocking neuronal activity. Furthermore, in vivo neuronal expression of mutated nmnat shows that enzymatically inactive NMNAT protein retains strong neuroprotective effects and rescues the degeneration phenotype caused by loss of nmnat. Our data indicate an NAD-independent requirement of NMNAT for maintaining neuronal integrity that can be exploited to protect neurons from neuronal activity-induced degeneration by overexpression of the protein.